Environmental Impact Assessment (EIA) : Guidelines for Shoreline Development Activities - Malaysia Jabatan Perlindungan Alam Sekitar author 482513; Malaysia Jabatan Perlindungan Alam Sekitar issuing body 482513 (Kota Kinabalu, Sabah : Environment Protection Department (EPD), 2012)
These guidelines provides an overview of the most important environmental issues, impacts, mitigation measures and monitoring programmes that need to be considered in connection with the shoreline development activities.